(untitled) (Canadian Medical Education Journal, 2023)
Faculty development in medical education is often delivered in an ad hoc manner instead of being a deliberately sequenced program matched to data-informed individual needs. In this article, the authors, all with extensive experience in Faculty Development (FD), present a competency-based faculty development (CBFD) framework envisioned to enhance the impact of FD. Steps and principles in the CBFD framework reflect the lessons learned from competency-based medical education (CBME) with its foundational goal to better train physicians to meet societal needs. The authors see CBFD as a similar framework, this one to better train faculty to meet educational needs. CBFD core elements include: articulated competencies for the varied educational roles faculty fulfill, deliberately designed curricula structured to build those competencies, and an assessment program and process to support individualized faculty learning and professional growth. The framework incorporates ideas about where and how CBFD should be delivered, the use of coaching to promote reflection and identity formation and the creation of communities of learning. As with CBME, the CBFD framework has included the important considerations of change management, including broad stakeholder engagement, continuous quality improvement and scholarship. The authors have provided examples from the literature as well as challenges and considerations for each step.